Perilaku Politik Masyarakat dalam Pilkades Gunung Tiga OKU - Aginda, Runa (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study describes the political behavior of the community in the election of the village head of Gunung Tiga Village, Ulu Ogan District, OKU Regency for the 2020-2026 Period. The formulation of the problem in this research are: 1. political behavior of the people of Gunung Tiga Village, in the 2020 village head election, 2. What factors influence political behavior in village elections, the people of Gunung Tiga Village, Ulu Ogan District, Ogan Komering Ulu Regency. The method used in this study is a quantitative method to determine voter behavior by distributing questionnaires to the people of Gunung Tiga Village using a voter behavior approach. This approach aims to determine the results of voting behavior in the people of Gunung Tiga Village. This research can be concluded that the political behavior of the people of Gunung Tiga Village can be broadly classified into three sociological, psychological, and rational choice aspects. Sociological approaches based on the community conduct elections by looking at the regional background of the candidate for the village head and there are also ethnic background factors that influence people's choices.